Produksi Biskuit Limbah Tanaman Jagung Sebagai Pakan Komersil Ternak Ruminansia - Yuli Retnani; Indah Wijayanti; Nur Rochmah Kumalasari (Institut Pertanian Bogor, 2011)
Biscuit is one of feed wich is forming by heating and pressing that can be reduce size and volume of forage, so its easy to handling and storage. The objective of this study was to produce corn leaf and field grass to be biscuit form as a commercial feed ruminant and was to evaluate biscuit feeding of corn leaf and field grass for feed intake, body weight gain and feed efficiency of sheep. This research divided in two phases, i.e. production of Corn Plant Waste Biscuit and productivity feed biscuit technology in field scale (MT Farm Ciampea) on April-November 2010. Experimental diets for the second phase used Completely Randomized Design with 3 treatments dan 3 replications were T1 = biscuit (100% field grass); T2 = biscuit (50% field grass + 50% corn leaf); T3 = biscuit (100% corn leaf). The second phase of experimental used the best biscuits treatment in the first phase. The average of biscuit machine production capacity was 8.6 kg/h with the production cost of Rp 1072,-/kg. The results showed that biscuit of corn leaf 100% had best nutrient quality with crude protein 17.97%, crude fiber 28.20%, crude fat 1.09% and BETN 40.99%. Mean while, physic quality test showed that water content was 13.10%, water activity was 0.866%, density was 0.529 g/ cm3, and water absorption capacity was 78.58%. Productivity test on sheep fed field grass and corn leaf biscuit showed that nutrient quality analysis showed that best quality was corn leaves biscuit with Corn leaves biscuit fed has significant efficiency on dry matter intake (P<0.05) with was the highest value (263.18 g/head/day). The average of body weight gain of sheep fed with corn leaf biscuit was 61.90 g/head/day or 44.60% higher than sheep fed with field grass. The highest cost efficiency of sheep fed with corn leaf biscuit was Rp. 139.080,-. Demonstration plots on Subur Jaya Farm, Darmaga for 5 weeks showed that the highest IOFC on the sheeps fed biscuit than field grass.